Mechanical Fatigue Resistance of Piezoelectric PVDF Polymers - Shin, Youn-Hwan; Jung, Inki; Park, Hyunchul; Pyeon, Jung Joon; Son, Jeong Gon; Koo, Chong Min; Kim, Sangtae; Kang, Chong-Yun (MDPI, 2018)
The fatigue resistance of piezoelectric PVDF has been under question in recent years. While some report that a significant degradation occurs after 10(6) cycles of repeated voltage input, others report that the reported degradation originates from the degraded metal electrodes instead of the piezoelectric PVDF itself. Here, we report the piezoelectric response and remnant polarization of PVDF during 10(7) cycles of repeated compression and tension, with silver paste-based electrodes to eliminate any electrode effect. After applying repeated tension and compression of 1.8% for 10(7) times, we do not observe any notable decrease in the output voltage generated by PVDF layers. The results from tension experiments show stable remnant polarization of 5.5 C/cm(2), however, the remnant polarization measured after repeated compression exhibits a 7% decrease as opposed to the tensed PVDF. These results suggest a possible anisotropic response to stress direction. The phase analyses by Raman spectroscopy reveals no significant change in the phase content, demonstrating the fatigue resistance of PVDF.
Keywords: POLARIZATION FATIGUE; FILMS; PHASE